(untitled) (REMUNOM, 2025)
The objective of this article is to analyze how elementary school teachers use games and play activities in the teaching and learning process, highlighting the importance of playfulness. The study was motivated by the following research question: how can the use of games and play in mathematics teaching enhance children’s learning? Methodologically, this is a qualitative, exploratory field research, conducted through a structured questionnaire applied to teachers at a public school in Linhares, Espírito Santo, Brazil. Data collection was carried out using the Google Forms platform and the WhatsApp application. The analysis of the narratives was based on Content Analysis (Bardin, 2016). The results indicate that games and play activities significantly contribute to the mathematics teaching and learning process, stimulating logical-mathematical reasoning, encouraging students’ active participation, and promoting knowledge construction.